KARAKTERISTIK KIMIA DAN MIKROBIOLOGI SEDIAAN OPAQUE SOAP DENGAN PENAMBAHAN EKSTRAK ETANOL TEMBAKAU - Andi Eko Wiyono; Herlina Herlina; Andrew Setiawan Rusdianto; Mega Desy Safitri (JURNAL AGROTEKNOLOGI, 2021)
Opaque soap is a solid soap product. It was made from a mixture of oil and the addition of alkaline compounds to form a saponification process. Solid soap preparations made with the addition of tobacco extract as an active ingredient that contains nicotine compounds, which include toxic alkaloids are weakly basic. In addition, tobacco extracts chosen to produce products that were beneficial to society. The purpose of this study was to provided wider use of tobacco and to know the characteristic of opaque soap preparations with the addition of tobacco extracts. The research method was a single completely randomized design (CRD) with descriptive analysis. In this study, the formulas of opaque soap were A0 (no addition of tobacco extract), A1 (1.2 g of tobacco extract), A2 (2.4 g of tobacco extract), and A3 (4.8 g of tobacco extract). The observed parameters were chemical and microbiological characteristics. All variations of opaque soaps had a pH of 9.51-9.77, water content of 13.15%-14.35%, free alkali 0.056-0.0584, antibacterial (E. coli inhibition zone proved by clear zone) about 8.60-21.50 mm; and nicotine levels 0-383.67 mg/100g. From the results due to chemical and microbiological characteristics, all of the opaque soap with additional tobacco extract was in accordance with the Indonesian National Standards (SNI 3532-2016) so that soap was safe for use by the public. Keywords: chemistry, microbiology, soap preparations, tobacco extract